Unstable angina pectoris hastalarında signal peptide complement C1R/C1S, UEGF, ve BMP1 epıdermal growth factor-like domain-containiing protein 1' in tanısal değerinin araştırılması / Diagnostic value of signal peptide complement C1R/C1S, UEGF, and BMP1 epidermal growth factor like domain containing protein in unstable angina pectoris patients - ÖZKAN, Abuzer (My University, 2015)
Objective: SCUBE1 has been used as biomarker for the diagnoses of acute coronary syndrome in some recent studies. This study aim to determine whether SCUBE 1 is effective for the discrimination of patient with USAP symptoms from non ST elevated myocardial infarction (NSTEMI) and non cardiac chast pain (NCCP) patient. Materials And Methods: Our study group consist of the patients who comes emergency service and cardiology service outpatient clinics with complaint of possible acute coronary syndrome. We evaluated the patient with anamnesis, physical examination, laboratory and ekg findings; then divided them into 5 groups as USAP, NSTEMİ, ST elevated myocardial infarction (STEMI), NCCP patient ( totally 185 patient) and healthy ones ( 45 patients ) by using criteria in the American Heart Association ( AHA) guide. We studied SCUBE 1 values with patients admission blood in all the groups. Findings: There has been no significant difference between cave groups and control group (p = 0.630). Troponin values has been found higher in the patients group with significance ( p < 0,001 ). We found no significant difference when we compared SCUBE 1 values in the USAP groups by using GENSİNİ and Global Registry of Acute Coronary Events (GRACE) scoring systems (p = (0.485), (0.932), (0.585)). Results: There has been no significant correlation that may change the prognosis of the patients between SCUBE 1 values, clinical scoring and biochemical parameters. We also found that SCUBE 1 is not a parameter that can predict acute coronary syndrome (ACS) in patients with chest pain. More comprehensive studies should be done to use SCUBE 1 in acute coronary syndrome. Keywords: Acute Coronary Syndrome, SCUBE 1, GENSINI Scoring, GRACE Scoring.
Diagnostic value of signal peptide complement C1R/C1S, UEGF, and BMP1 epidermal growth factor like domain containing protein in unstable angina pectoris patients
Amaç: Sıgnal peptıde complement c1r/c1s, uegf, and bmp1 - epıdermal growth factor - lıke domaın - contaınıng protein 1 (SCUBE1) yakın zamanda bazı çalışmalarda Akut koroner sendromun tanısında biyobelirteç olarak kullanılmıştır. Bu çalışmanın amacı unstable angına pectorıs (USAP) kliniği ile başvuran hastaların; ST elevasyonu olmayan miyokart enfarktüsü (NSTEMI) ve kardiyak dışı göğüs ağrılı (NCCP) hastalardan ayrımında SCUBE1‗in etkili olup olmadığını araştırmaktır. Materyal ve Metot: Çalışma grubumuz, acil servis ve kardiyoloji polikliniğine göğüs ağrısı ve akut koroner sendrom düşündüren şikayet ile başvuran hastalardan oluşmuştur. Hastalar anamnez, fizik muayene, laboratuar tetkikleri ve EKG bulguları ile değerlendirilerek Amerika Kardiyoloji Derneği (AHA) kılavuzlarına göre USAP, NSTEMI, ST elevasyonlu miyokart enfarktüsü (STEMI) ve NCCP olarak toplamda 185 hasta ve 45 sağlıklı olarak 5 gruba ayrıldı. Tüm gruplardan başvuru esnasında alınan kan örneklerinden SCUBE1 değerleri çalışıldı. Bulgular: SCUBE1 değerleri açısından hasta grupları ile kontrol grubu karşılaştırıldığında anlamlı fark görülmedi (p = 0.630). Troponin değerleri hasta gruplarında kontrol grubuna göre anlamlı oranda yüksek bulundu (p < 0.001). USAP grubunda SCUBE1 degerleri, GENSİNİ Skorlama ve Global Registry of Acute Coronary Events (GRACE) risk skorlaması açısından kıyaslandığında anlamlı fark çıkmadı (p = (0.485), (0.932), (0.585)). Sonuç: Çalışmamızda SCUBE1 değerleri ile biyokimyasal parametreler ve klinik skorlamalar arasında hasta kliniğine yön verecek anlamlı bir korelasyon oluşmadı. Gruplar arasında da SCUBE1 değerleri' nin göğüs ağrılı hastalarda akut koroner sendromu (AKS) öngördürecek bir parametre olmadığını saptadık. SCUBE1' in AKS' lerde kullanılabilmesi için daha kapsamlı çalışmalar yapılmalıdır. Anahtar Kelimeler: Akut Koroner Sendrom, SCUBE1, GENSİNİ Skorlaması, GRACE Skorlaması.
Keywords: MEDICINE; Kardiyoloji